Positive effects of dietary Clostridium butyricum supplementation on growth performance, antioxidant capacity, immunity and viability against hypoxic stress in largemouth bass - Li, Peijia; Chen, Xiaoying; Hou, Dongqiang; Chen, Bing; Peng, Kai; Huang, Wen; Cao, Junming; Zhao, Hongxia (Frontiers in Immunology, 2023)
The effects of dietary supplementation of Clostridium butyricum (CB) on growth performance, serum biochemistry, antioxidant activity, mRNA levels of immune-related genes and resistance to hypoxia stress were studied in largemouth bass. Feed with CB0 (control, 0 CFU/kg), CB1 (4.3×108 CFU/kg), CB2 (7.5×108 CFU/kg), CB3 (1.5×109 CFU/kg) and CB4 (3.2×109 CFU/kg) CB for 56 days, and then a 3 h hypoxic stress experiment was performed. The results showed that dietary CB significantly increased the WGR (weight gain rate), SGR (specific growth rate), PDR (protein deposition rate) and ISI (Intestosomatic index) of largemouth bass (P<0.05). Hepatic GH (growth hormone)/IGF-1 (insulin-like growth factor-1) gene expression was significantly upregulated in the CB3 and CB4 groups compared with the CB0 group (P<0.05), while the FC (feed conversion) was significantly decreased (P<0.05). Serum TP (total protein) and GLU (glucose) levels were significantly higher in the CB4 group than in the CB0 group (P<0.05), while the contents of serum AST (aspartate transaminase), ALT (alanine transaminase), AKP (alkline phosphatase) and UN (urea nitrogen) in CB4 were significantly lower than those in CB0 (P<0.05). T-AOC (total antioxidant capacity), SOD (superoxide dismutase), CAT (catalase), POD (peroxidase) and GSH-Px (glutathione peroxidase) activities were significantly higher in CB3 and CB4 groups than in CB0 group (P<0. 05). The liver MDA (malondialdehyde) content of CB1, CB2, CB3 and CB4 groups was significantly higher than that of CB0 group (P<0. 05). The relative expressions of IL-1β (interleukin 1β), TNF-α (tumor necrosis factor α) and TLR22 (toll-like receptor-22) genes in CB2, CB3 and CB4 groups were significantly lower than those in CB0 group (P<0.05). The relative expression of IL-8 (malondialdehyde) and MyD88 (Myeloid differentiation factor 88) genes in the CB4 group was significantly lower than that in the CB0 group (P<0.05). The liver LZM (lysozyme) content of CB2, CB3 and CB4 groups was significantly higher than that of CB0 group (P<0. 05). The relative expression of IL-10 (interleukin 10) and TGF-β (transforming growth factor β) genes in the CB4 group was significantly higher than that in the CB0 group (P<0.05). Under hypoxic stress for 3 h, the CMR of CB0 group was significantly higher than that of CB1, CB2, CB3 and CB4 groups (P<0.05). Dietary CB can improve the growth performance and resistance to hypoxic stress of largemouth bass by regulating the expression of GH/IGF-1 gene and inflammatory factors and inhibiting TLR22/MyD88 signaling pathway.